Capturing the diversity of Mediterranean farming systems prior to their sustainability assessment: The case of Cyprus. (July 2020) - Stylianou, Andreas; Sdrali, Despina; Apostolopoulos, Constantinos D.
Highlights: We identify six farming system types in Cyprus using multivariate analysis. Results question the effectiveness of CAP subsidies for higher farm profitability. Off/no-farm income is sought for survival but not to cross-subsidize the farm. The importance of group membership for farm survivability is highlighted. There is weak complementarity and trade-offs between the main household components. Abstract: Prior to any sustainability assessment and/or any effort to understand or develop the agricultural sector, the acknowledgment of the diversity of farming systems (FSs) is crucial. Typologies are often used for this purpose. The goals of this study were, for the first time, to identify and characterize the divergent FSs that exist in southeastern Cyprus, and analyse the main drivers of variability among FSs. Beyond this empirical exploration, this study explores the suitability of typology delineation for understanding the heterogeneity of FSs prior to their sustainability assessment and for the potential of adoption of sustainable intensification technologies. The multivariate statistical techniques of principal component analysis and cluster analysis were employed on data from a representative sample of 324 farms in the study area. Results proposed six FSs, differentiated by land use, livestock, production pattern, farm, household, labour and economic variables. FS1-FS4 were crop-oriented and FS5-FS6 were livestock-oriented cultivating cereals and fodder crops for on-farm consumption. Only FS1 was profitable without subsidies, which were negatively associated with economic results. This casts doubt on the effectiveness of subsidies in providing the basis for a more profitable agricultural sector. FS3-FS5 households sought off/no-farm income mainly for their survival (i.e. complementary source of income), but not to cross-subsidize the farm. Small crop-oriented farms (FS4) and medium-sized livestock-oriented farms (FS5) had several weaknesses, such as elderly, low-educated managers and low profitability; thus, their viability should be the priority of decision makers. It was also observed a weak complementarity between the main system components (crop, livestock, off/non-farm income), which might negatively affect sustainable intensification. The importance of group membership for farm sustainability was also highlighted. The results of this study can be used for a more focused agricultural policy, tailored to the different constraints and opportunities of FSs, but also to inform public decision makers who are responsible to design and implement agricultural policy in Cyprus, or in other European Mediterranean regions with similar FSs and agro-ecological conditions.